"Can I drive, doctor?" LEAN thinking may help us answer the question. Issue 2 (16th March 2009) - Thomas, R H; Hughes, T A T
Abstract : The loss of a driving licence can have a devastating effect on an individual's domestic life and work. Driving is a complex composite function comprising a number of other complex composite functions, and it is difficult to predict driving ability just from the traditional neurological examination. We propose the acronym LEAN as an aide-memoire to help structure a suggested driving section in the routine neurological clerking, and to help unpack the concept of "fitness" to drive: L icence status, E ligibility (to drive), A bility (to drive) and N otification requirements (to the licensing authorities), now and in the future; cover most of the important issues and may help ensure that people get the best advice. If there are concerns about someone's driving ability, with or without vehicle adaptations, an assessment in a Disabled Drivers Assessment Unit is recommended.